(untitled) (Scientific journal of the Fergana State University, 2026)
Measurements of electrical conductivity and the Hall effect are systematically used to study the number of defects arising under the influence of hard radiation, as well as to obtain information about the system of energy levels of defects. The body of data obtained from experiments conducted on germanium and silicon crystals, as well as on other semiconductors, convincingly demonstrates that radiation defects (even in the theoretically simplest case of electron bombardment) have a complex spectrum of shallow and deep energy levels in the band gap. The presence of multiple deep defect levels in crystals with a sufficiently wide band gap is qualitatively explained by extending the concept of a decrease in the electron binding energy in a medium with high permittivity to the case of multiple ionization (for example, for an interstitial Ge or Si atom). Similarly, unfilled valence bonds in the region of an empty site (vacancy) are believed to lead to the existence of multiple electron trapping levels.